Answer: 4.14*10^-4 m
Step-by-step explanation:
n = N / L, where N = l/2r. So that
n = (l/2r) / L
n = 1/2r
Also, we know that
B = μnI. Substituting for n, we have
B = μI / 2r. If we make r subject of formula
r = μI / 2B
Recall, V = IR, and I = V/R, substituting for I
r = μV / 2BR
Also, ρ = RA/L, and R = ρL / A
substituting R also, we have
r = μVA / 2BρL
A can also be represented as, πr², so that we have
r = μVπr² / 2BρL
1 = μVπr / 2BρL, making r subject of formula again, we have
r = 2BρL / μVπ
r = (2 * 6.69*10^-3 * 1.59*10^-8 * 23) / (4π*10^-7 * 3 * π)
r = 4.89*10^-9 / 1.18*10^-5
r = 4.14*10^-4 m